Sisters by choice - Mallery, Susan (Toronto, ON Mira, 2020)
"After her cat toy empire goes up in flames, Sophie Lane returns to Blackberry Island, determined to rebuild. Until small-town life reveals a big problem: she can't grow unless she learns to let go. If Sophie relaxes her grip even a little, she might lose everything. Or she might finally be free to reach for the happiness and love that have eluded her for so long. Kristine has become defined by her relationship to others. She's a wife, a mom. As much as she adores her husband and sons, she wants something for herself--a sweet little bakery just off the waterfront. She knew changing the rules wouldn't be easy, but she never imagined she might have to choose between her marriage and her dreams." -- Amazon.
Includes discussion questions.
Includes excerpt from The Friendship List.
108187
Keywords: Sisters -- Fiction; Mothers and daughters; Man-woman relationships; Interpersonal relations; Islands; Washington (State); Domestic fiction